Effect of geometrical size on the tensile strength of finger joint / Shamsiah Suib - Suib, Shamsiah (2002)
The objective of this study is to analyse the strength of finger joint using Finite Element Analysis under tensile load with different geometrical size which have different length, pitch and tip of finger joint. The analysis will use program LUSAS 13 for the selected types of model which contains modules for designing the finite element mesh modes for performing the analysis itself, and for analyzing and post-processing the results. The computer output analyzed the stresses and displacement of all model and strength of finger joints is largely influenced by the outermost finger. The Modulus of Elasticity of the finger joint can be obtained by analyzing the displacement of the joint to get the stress - strain relationship. It can be concluded that when tip/pitch ratio is higher, the tensile strength reduces while when length/pitch ratio is higher, the stress concentration is higher too.